Integrative Taxonomy, Phylogeny, and New Species of the Weevil Genus Onyxacalles Stüben (Coleoptera: Curculionidae: Cryptorhynchinae) - Peter E. Stüben; Jonas J. Astrin (Psyche: A Journal of Entomology)
A molecular phylogeny of the western Palearctic weevil genus Onyxacalles Stüben, 1999 is presented, combining two mitochondrial genes (COI and 16S) in a Bayesian analysis. Based on molecular data, Onyxacalles pyrenaeus Boheman, 1844 is transferred into the genus Kyklioacalles Stüben 1999 (K. fausti group) and—in an integrative taxonomy framework—the interaction between morphology and molecular analysis is illustrated. The species of Onyxacalles s. str. are assigned to three new species groups, O. henoni, O. luigionii, and O. portusveneris groups. The distribution of the related species in the Mediterranean area is illustrated with values of COI and 16S p-distances. Three new species are described and distinguished from their related species: Onyxacalles nuraghi Stüben sp.n. from Italy (Sardinia), Onyxacalles torre Stüben and Astrin sp. n. from France (Corsica) and Onyxacalles vilae Stüben sp. n. from Croatia (Velebit Mts.). A catalogue of all 20 species of Onyxacalles is given, and a key is finally presented combined with image stacking of the habitus and aedeagus for all species.